3D Model of Tunku Tun Aminah Library Using Unmanned Aerial Vehicle (UAV) - Ahmad Kamal, `Abdul `Aziz; Ahmad, Mustaffa Anjang; Ahmad, Mohd. Juraidi; Srivanit, Manat (International Journal of Sustainable Construction Engineering and Technology, 2023)
3-Dimensional (3D) modelling helped bring flat, 2D ideas to life. 3D models were valuable because they could include a much wider array of project information. The purpose of this study was to develop a 3D model by using Unmanned Aerial Vehicle (UAV) images of Tunku Tun Aminah (PTTA) Library building. To create a 3D model, Agisoft Metashape software combined photos from UAV images. Then, we assessed the accuracy of the 3D model of Tunku Tun Aminah's library building to the actual scale of the building from a vertical and horizontal view. The result of the 3D model that has been constructed demonstrates a high level of accuracy in capturing its intricate details and spatial characteristics. The vertical and horizontal views, both the Tunku Tun Aminah library and the parking lots had actual lengths that matched the estimated values precisely. Theresults indicated that there were slight differences in measurements, and all the measurements were 95% accurate and above. The precision demonstrated in capturing the dimensions of these structures indicates reliable data for analysis and decision-making purposes. The Ground Sampling Distance (GSD) for the assessment was 1.36 cm per pixel. At the end of this research, the 3D model of PTTA library was uploaded on SketchFab to allow various parties, including university authorities, contractors, local authorities, architects, and structural engineers to have a better understanding of the building’s condition and its surroundings.